Supporting children who have a parent with a mental illness in Tyrol: a situational analysis for informing co-development and implementation of practice changes - Ingrid Zechmeister-Koss; Melinda Goodyear; Heinz Tüchler; Jean Lillian Paul (BMC, 2020)
Abstract Background A research project, which aims to improve the situation of children of parents with a mental illness (COPMI) is currently underway in the Austrian region of Tyrol. The project aims to strengthen formal and informal support structures around the child, through enhancing their village of collaborative support. Understanding the current situation in the region is vital for implementing practice change. This paper aims to gain knowledge regarding the Tyrolean societal and service provision context. Methods We collected qualitative (17 interviews among stakeholder and people with lived experience) and quantitative data (e.g. health insurance data) regarding overall societal characteristics, epidemiology of mental illness, currently existing services, uptake of services, and current practices and challenges of identifying and supporting COPMIs. We analysed data along eight external context dimensions: 1) professional influences, 2) political support, 3) social climate, 4) local infrastructure, 5) policy and legal climate, 6) relational climate, 7) target population, and 8) funding and economic climate. Results We identified that there is awareness of potential challenges related to COPMIs at both a professional and planning level. Additionally, there is a lack of installed support processes and standards to meet these children's needs across Tyrol. A variety of services are available both for unwell parents, as well as for families and individual family members. Yet, only one small service addresses COPMIs directly. Services fall into different sectors (education, health, social affairs) and are funded from different sources, making coordination difficult. Access varies from universal to rather restricted (i.e. through referral). The potential number of parents which could be reached in order to identify their children via adult mental health, differs considerably by setting. Societal structures indicate that the informal and voluntary sector may be a realistic source for supporting COPMIs. Conclusions The societal structures and the current services provide a rich resource for improving identification and support of COPMIs, however considerable coordination and behaviour change efforts will be required due to the fragmentation of the system and professional cultures. The insights into the context of supporting COPMIs have been of high value for developing and implementing practice changes in the local organizations.